Biotechnology industry as a catalyst for circular economy in India - John Festus Vandy; Sasmita Mohanty; Shibani Mohapatra (Discover Sustainability)
Abstract The biotechnology industry in India plays a pivotal role in advancing the principles of a circular economy by fostering sustainable practices and innovation. The sector minimizes resource consumption and waste production by applying advanced technologies such as bio-based materials, waste valorization, renewable energy, and bioremediation. The leading uses of this technology involve transforming agricultural and industrial waste materials into valuable products. The production of biofuels, bioplastics, and biofertilizers helps to lower our reliance on fossil fuels and chemical-heavy procedures. Biotechnology-driven solutions enable industries like agriculture, healthcare, and manufacturing to recycle and reuse resources efficiently. Policy supports and growing investments create a strong foundation for India’s biotechnology sector enabling it to tackle environmental issues while driving sustainable economic development. The research examines how biotechnology in India supports circular economic development through successful projects and explores existing challenges and potential future advancements. Using a Content Analysis approach, this study concludes that while the Biotechnology Industry demonstrates a strong alignment to CE principles and its adoption and application in key sectors, thereby making significant socio-economic contributions, its full potential will require targeted reforms in regulatory systems, public–private partnerships, and enhanced investments in innovations. These reforms could position India as a global leader in a Biotechnology-driven CE transition.